PRR11 unveiled as a top candidate biomarker within the RBM3‐regulated transcriptome in pancreatic cancer - Sofie Olsson Hau; Sara Wahlin; Sophie Cervin; Vilgot Falk; Björn Nodin; Jacob Elebro; Jakob Eberhard; Bruce Moran; William M Gallagher; Emelie Karnevi; Karin Jirström (Wiley, 2022)
Abstract The outlook for patients with pancreatic cancer remains dismal. Treatment options are limited and chemotherapy remains standard of care, leading to only modest survival benefits. Hence, there is a great need to further explore the mechanistic basis for the intrinsic therapeutic resistance of this disease, and to identify novel predictive biomarkers. RNA‐binding motif protein 3 (RBM3) has emerged as a promising biomarker of disease severity and chemotherapy response in several types of cancer, including pancreatic cancer. The aim of this study was to unearth RBM3‐regulated genes and proteins in pancreatic cancer cells in vitro, and to examine their expression and prognostic significance in human tumours. Next‐generation RNA sequencing was applied to compare transcriptomes of MIAPaCa‐2 cells with and without RBM3 knockdown. The prognostic value of differentially expressed genes (DEGs) was examined in The Cancer Genome Atlas (TCGA). Top deregulated genes were selected for further studies in vitro and for immunohistochemical analysis of corresponding protein expression in tumours from a clinically well‐annotated consecutive cohort of 46 patients with resected pancreatic cancer. In total, 19 DEGs (p < 0.01) were revealed, among which some with functions in cell cycle and cell division stood out; PDS5A (PDS cohesin associated factor A) as the top downregulated gene, CCND3 (cyclin D3) as the top upregulated gene, and PRR11 (proline rich 11) as being highly prognostic in TCGA. Silencing of RBM3 in MiaPaCa‐2 cells led to congruent alterations of PDS5A, cyclin D3, and PRR11 levels. High protein expression of PRR11 was associated with adverse clinicopathological features and shorter overall survival. Neither PDS5A nor cyclin D3 protein expression was prognostic. This study unveils several RBM3‐regulated genes with potential clinical relevance in pancreatic cancer, among which PRR11 shows the most consistent association with disease severity, at both transcriptome and protein levels.